Variability in Practice and Implementation of Oxygen Target Saturation Policies in United States' Neonatal Intensive Care Units - Parikh, Pratik; White, Robert D.; Tolia, Veeral N.; Reyburn, Brent; Guillory, Charleta; Ahmad, Kaashif A. (American Journal of Perinatology, 2024)
Objective This study aimed to describe target oxygen saturation (SpO2) ranges used for premature infants in United States' neonatal intensive care units (NICUs) and to describe if these target SpO2 ranges have changed in recent years.Study Design A 29-question survey focused on target SpO2 practices and policies was distributed via the NICU medical directors listservs for the American Academy of Pediatrics Section of Neonatal-Perinatal Medicine and Pediatrix Medical Group between August and October of 2021. Results were collected via Research Electronic Data Capture (REDCap).Results We received responses representing 170 unique, levels 2, 3, and 4 NICUs from 36 states. Most NICUs (130, 78%) have recently changed their SpO2 targets in response to target SpO2 clinical trials. Over time, the most commonly reported target SpO2 range has shifted from 88–92% to 90–95. Of NICUs that changed limits, the most common lower SpO2 limits increased from 88 to 90% and the upper SpO2 limits changed from 92 to 95%. The interquartile range for lower SpO2 limit shifted from 85–88% to 88–90% and the IQR for upper SpO2 limit decreased from 92–95 to 94–95%. Most NICUs had designated conditions that would allow for deviations from standard target SpO2 ranges. These most commonly include pulmonary hypertension (152, 95%), severe bronchopulmonary dysplasia (81, 51%), and retinopathy of prematurity (51, 32%).Conclusion Oxygen saturation limits have changed over time with an overall increase in targeted SpO2. However, there remains considerable interunit variation in SpO2 policies. There is a need to achieve consensus to optimize clinical outcomes.Key Points
Keywords: oxygen saturation; oxygen target saturation ranges; alarm limits; retinopathy of prematurity